Be a professional - Senathirajah, Kuna; VStudios ([S.l.] : VStudios, 2008)
Kuna Senathirajah captives in this enlightening video about the virtues of professionalism. In this day and age, excellence and expertise are simultaneously necessary and hard to find. Kuna teaches us the value of our work and how we can take our performance to the next level. Being a professional has nothing to do with what kind of job you have. Professionalism is an attitude towards work that sets you apart from the mediocre and above the rest
Title from title screen
DVD format
Keywords: Ethics, Professional; Professional ethics; Multilevel marketing; Direct marketing